The post-Covid urban heritage, between attractiveness and risks, Case of the city of Constantine - Algeria - Bourecherouche , Meriem; Fertas, Lahcene (Technium Social Sciences Journal, 2022)
The aim of this research is to find out and analyze the reasons for the stagnation of the tourist attractiveness of the urban tourist heritage of the city of Constantine (the old city), and try to make objective suggestions so as to activate the attractiveness of the urban touristic heritage of the city of Constantine all over again, particularly after the Corona crisis that has put the tourism sector in the city into an almost total immovability. In this regards, a questionnaire was used as a tool for the study, and in order to obtain and analyze information through the selected sample of the city’s population. In virtue of which, the results obtained from this study lead to diagnosing the complex problems of the tourists’ urban heritage along with the various risks threatening the same, which negatively affected the city’s tourist attractiveness; inclusive of negative human behaviours, in respect such as disrespecting the values of this heritage and various illegal practices on its spaces, in addition to weak governance and management mechanisms, thus making the city’s urban heritage in a waiting state.